Beyond CAR-T Cells: exploring CAR-NK, CAR-M, and CAR-γδ T strategies in solid tumor immunotherapy - Hou, Yingjie; Hu, Shihua; Liu, Chong; Chen, Xin; Wang, Yuru; Li, Youzherui; Fu, Zihe; Feng, Chunjing; Gong, Yanhua; Liu, Zichuan; Peng, Shouchun (Frontiers in Immunology, 2025)
Adoptive cell therapy (ACT) employing chimeric antigen receptor (CAR) engineering represents a transformative advancement in cancer immunotherapy. CAR-T cell therapies have demonstrated significant clinical success in hematological malignancies, yet their application to solid tumors faces persistent challenges. Key limitations include the paucity of tumor-specific antigens, poor intratumoral infiltration, immunosuppressive tumor microenvironment (TME), and treatment-related toxicities such as cytokine release syndrome (CRS) and neurotoxicity. In contrast, CAR natural killer (CAR-NK) cells show promise in solid tumors such as ovarian, pancreatic, and glioblastoma, with encouraging preclinical and early clinical evidence, although limited persistence and antigen heterogeneity remain major challenges. Unlike CAR-T cells, CAR-NK therapies mediate tumor clearance through both cytotoxic (e.g., granzyme/perforin release) and cytokine-mediated mechanisms while mitigating toxicity risks. Their lack of human leukocyte antigen (HLA) dependency enables “off-the-shelf” manufacturing from allogeneic donors, circumventing patient-specific production bottlenecks. CAR-macrophage (CAR-M) therapies further address solid tumor barriers by leveraging innate phagocytic clearance, antigen-presenting functions, and TME penetration. Macrophages inherently infiltrate hypoxic tumor regions and remodel stromal barriers, enabling CAR-Ms to synergize with adaptive immunity by cross-priming T cells. Preclinical models highlight CAR-M efficacy in depleting immunosuppressive tumor-associated macrophages (TAMs) and reversing TME-driven immune evasion. Emerging CAR- Gamma-Delta T (CAR-γδ T) cell therapies combine CAR-mediated antigen specificity with the intrinsic tumoricidal activity of γδ T cells, which recognize stress-induced ligands independently of major histocompatibility complex (MHC) presentation. This dual-targeting capability enhances tumor selectivity while reducing on-target/off-tumor toxicity. This review systematically examines cellular sources, mechanistic advantages and clinical progress. By evaluating these platforms’ complementary strengths, we propose rational strategies for integrating CAR-NK, CAR-M, and CAR-γδ T cells into tailored therapeutic regimens for solid tumors.